Kenya Economic Update, April 2018, No. 17 : Policy Options to Advance the Big 4 - World Bank Group (World Bank, Nairobi, 2018)
After multiple headwinds dampened growth in 2017, a nascent rebound in economic activity in Kenya is gaining momentum. Notwithstanding the projected rebound in economic activity risks are tilted to the downside. The Government of Kenya has outlined four big priority areas for the next five years. These are agricultural and food security, affordable housing, increased share of manufacturing, and universal health coverage. Support from the public and more importantly the private sector will be required to achieve the big 4. Specific measures to create fiscal room to support the big 4 can include: enhancing domestic revenue mobilization through the rationalization of tax exemptions; slowing the pace of expansion of recurrent spending; and improving the efficiency of spending. Boosting agricultural productivity and food security will require re-allocating more resources to agriculture and improving the efficiency of current spending in the sector. To eradicate poverty by 2030, Kenya will need a combination of higher growth, more inclusive growth, and growth that is increasingly driven by the private sector and translates into more rapid poverty reduction.